(untitled) (Global Journal of Science Frontier Research, 2023)
The most reliable and widely used diastereomer method in chiral discrimination has a fatal problem in that it is impossible to discriminate the diastereomers having chiral centers separated by more than 4 bonds The problem has been assumed to be intrinsic to the diastereomer method and therefore very difficult to solve In order to solve the problem we have developed highly potent chiral discrimination methods by use of helically chiral derivatization reagents for example A Fig 1 1 A has an anthracene-2 3-dicarboximido group on one side wing and OH or COOH group for derivatization on the other side wing The anthracene-2 3-dicarboximodo group is for highly sensitive fluorescence and long-distance anisotropy for 1H-NMR study